In Search of Better Opportunities : Sorting and Agglomeration Effects among Young College Graduates in Colombia - Bacolod, Marigee; De la Roca, Jorge; Ferreyra, Maria Marta (World Bank, Washington, DC, 2020)
This paper studies the dynamic sorting of workers prior to labor market entry that leads to skill differences across cities of different sizes, as well as its consequences on the estimation of agglomeration effects. Using rich administrative data for young, college-educated workers in Colombia, the paper shows that the most talented and best trained sort to big cities primarily because they attend college there and remain for work. The availability of colleges in an individual's high school city, parental resources, and high school city size are the most important determinants of the decision to move for college. The relatively less able remain in medium and small cities or move there for work after attending college in big cities. Pre-labor market sorting thus concentrates population and skill in big cities. As a result of this sorting, agglomeration effects are stronger for college than work city size, even after controlling for mediating factors such as individual ability or college selectivity.